2015
DOI: 10.1111/aas.12468
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous ketamine during spinal and general anaesthesia for caesarean section: systematic review and meta‐analysis

Abstract: We conclude that ketamine enhances post-operative analgesia after caesarean section under spinal anaesthesia. There is a paucity of data for several maternal adverse effects as well as for neonatal well-being. Further studies are needed for general anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 35 publications
1
31
0
1
Order By: Relevance
“…ketamine administered during surgery (0.15e1 mg kg À1 ), placebo, or other interventions were compared with respect to the incidence of post-Caesarean pain. 112 The analyses demonstrated that time to first analgesic request was significantly longer, and the visual analogue scale pain sores at rest 2 h after surgery performed under spinal anaesthesia were significantly lower in ketamine-treated women. No such effects were observed in the studies, in which general anaesthesia was used.…”
Section: Possible Preventive Interventionsmentioning
confidence: 92%
“…ketamine administered during surgery (0.15e1 mg kg À1 ), placebo, or other interventions were compared with respect to the incidence of post-Caesarean pain. 112 The analyses demonstrated that time to first analgesic request was significantly longer, and the visual analogue scale pain sores at rest 2 h after surgery performed under spinal anaesthesia were significantly lower in ketamine-treated women. No such effects were observed in the studies, in which general anaesthesia was used.…”
Section: Possible Preventive Interventionsmentioning
confidence: 92%
“…Additionally, given that 1 mechanism of opioid-induced hyperalgesia is phosphorylation and thus stimulation of the N-methyl-D-aspartate receptor by opioids, low-dose ketamine, which blocks the N-methyl-D-aspartate receptor, can be considered to potentiate the effects of the opioids without causing the hallucinations or nightmares that are associated with higher doses. 64,65 A single 10-mg dose of ketamine, given intraoperatively, has been shown to decrease pain scores 2 weeks after delivery. 66 Although the data regarding preoperative gabapentin (600 mg) is mixed and there is some concern about transfer into breast milk and postpartum side effects such as dizziness, the risk/benefit ratio in this population may favor its use.…”
Section: Unscheduled or Emergency Cesarean Delivery In Patients With Oudmentioning
confidence: 99%
“…Ketamine may not change Apgar scores or umbilical pH, although concerns remain regarding the effect of ketamine on neurodevelopment. 14 Additionally, ketamine is reported to increase uterine tone. 15 With widespread prospective trials, the frequency and significance of these concerns may be addressed.…”
Section: Discussionmentioning
confidence: 99%